Новые среднеазиатские виды пчел рода Andrena (Hymenoptera, Andrenidae) - Осычнюк, А.3. (Вестник зоологии, 1982)
Two Andrena (Ulandrena) bee species from Tajik and Turkmen SSR are described as new. A. (U.) mikhaili sp. n. is similar to Andrena leucorhina M o r. (=A. ravicollis Mor., syn. nov.), differs from it by smaller size and forewing antefureal nervulus; female differs from A. leucorhina by shagreened abdominal tergite 1 finer sculpture of the propodeum medial field apical part, denser apical stripes of tergites 1—4 etc., male—by antennal segments 3—4 size, straight apical margin of sternite 8, genital apparatus etc. A. (U.) nesterovi sp. n. — closely related to A. glaroela War., exactly differing from it by forewing antefurcal nervulus; female differs from A. glareola hy clypeal sculpture, wider and shorter ocular fissures, wide apical stripes of tergites 1—4 etc., male—by short antennal segment 3, rounded sternite 8 apex, genital apparatus completely white clypeus, etc.